Abundance of aedes mosquito in selected food courts in relation to dengue outbreak in Ampang Jaya / Nurul Diana Mohamad - Mohamad, Nurul Diana (2015)
Introduction: Dengue fever is major international public health concern caused by Aedes aegypti and Aedes albopictus in tropical and sub-tropical region, predominantly urban and semi-urban area. Urban state such as Selangor, Johor and Perak are main contributor to the high incidence rate of dengue fever in Malaysia. Although many studies have been conducted, most of them mainly focusing on highly populated residential and other urbanized area, neglecting other human favourite spots area by which at par in producing risk to the transmission of dengue virus. Objective: This study aimed to determine the abundance of Aedes mosquito in selected urban food cour:ts in relation to dengue outbreak in Ampang Jaya Municipal Council (AJMC) territorial area. Methodology: A cross sectional study was conducted in nine selected urban and semi-urban food courts in AJMC by using the Mosquito Larvae Trapping Devices (MLTDs) and dengue cases reported at localities adjacent to the food courts within the period of 2010 to 2014. The study was divided into several phases; preliminary data process, instrumentation preparation, field sampling, data collection process and data analysis. Results: The highest ML TD Index reported in urban food court with 42.81±5.11 (Level 4). In term of species, Aedes albopictus is more abundance compared to Aedes aegypti, but there is no significant difference observed between the ML TDs infestation indoor and outdoor of the urban and suburban food courts, (X2 (1, N=37) = 2.86, p>0.05). Conclusion: The highest ML TD Index is recorded in urban food court with the value of 42.81 ±5.11 as compared to suburban food courts 38.80±4.40.The highest RR was also recorded in urban food court with the value of 0.05 as compared to suburban with the lower value of RR=0.03 indicating that urban area are prone to experience dengue outbreak compared to suburban area.